Evaluasi Pelaksanaan Pembelajaran Kurikulum 2013 di Sekolah Dasar Kristen 03 Wonosobo Tahun Pembelajaran 2022/2023 - Rifatul Mahmudah (Journal on Education, 2023)
How is the implementation of learning at the Christian Elementary School 03 Wonosobo in the 2022/2023 school year ", the purpose of this study is to examine the evaluation of the implementation of learning at the Christian Elementary School 03 Wonosobo in the 2022/2023 school year.In general, the Big Indonesian Dictionary (1996: 272) evaluation means assessment. Meanwhile, according to Wirawan (2012: 7) evaluation is: "Research to collect, analyze, and present useful information about the object of evaluation, then assess it and compare it with evaluation indicators and the results are used to make decisions about the object of evaluation". This type of research is qualitative research, which is research whose main purpose is to describe the facts and characteristics of the object or subject under study systematically and accurately and precisely. In relation to the 2013 Curriculum Learning Assessment Management. This research is qualitative research. This model highlights gaps in program implementation. The success of learning is seen from the acquisition of student learning outcomes. Evaluation of the 2013 curriculum, planning is designed based on instructions from the government, and must explore all the potential and abilities of students and all norms of life. Implementation of the 2013 curriculum, learning is carried out holistically to achieve overall goals as well, so that all student potential will be explored which is listed in the four core competencies using various assessment instruments, Assessment in 2013 curriculum learning is based on scientific assessment that assesses all the potential possessed by students. Assessment is not only limited to test instruments, but also through various instruments.